2019
DOI: 10.1002/jbio.201800440
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography to detect acute esophageal radiation‐induced damage in mice: A validation study

Abstract: Radiation therapy for patients with non‐small‐cell lung cancer is hampered by acute radiation‐induced toxicity in the esophagus. This study aims to validate that optical coherence tomography (OCT), a minimally invasive imaging technique with high resolution (~10 μm), is able to visualize and monitor acute radiation‐induced esophageal damage (ARIED) in mice. We compare our findings with histopathology as the gold standard. Irradiated mice receive a single dose of 40 Gy at proximal and distal spots of the esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In this study, rehabilitation nursing was used to intervene patients undergoing radiotherapy for esophageal cancer. The results showed that the total effective rate of improving swallowing function in IG was 82.8% (53/64), significantly higher than 57.8% in the control group, which was consistent with the findings in stroke patients with hemiplegia [ 25 ]. Radiotherapy can cause different degrees of radiotherapy reaction during the treatment of esophageal cancer.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, rehabilitation nursing was used to intervene patients undergoing radiotherapy for esophageal cancer. The results showed that the total effective rate of improving swallowing function in IG was 82.8% (53/64), significantly higher than 57.8% in the control group, which was consistent with the findings in stroke patients with hemiplegia [ 25 ]. Radiotherapy can cause different degrees of radiotherapy reaction during the treatment of esophageal cancer.…”
Section: Discussionsupporting
confidence: 88%
“…The advent of the MR guided radiotherapy will greatly facilitate such studies and our work gives an indication of the kind of changes to expect in the esophagus. Furthermore, this study facilitated the comparison between MRI and OCT imaging modalities to detect ARIED [17], affecting future clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…In current clinical practice, ARIED is scored based solely on patient symptoms [13, 14]. ARIED can cause reduced food intake, nausea, dysplasia, odynophagia, anorexia, and other complications, which may interrupt treatment [3, 7, 1317]. Treatment interruptions can affect tumor control [15, 17] and can likely be avoided if we can detect ARIED prior to patients developing symptoms and start countermeasures over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical coherence tomography (OCT) is a recent, rapidly developing, high-definition light imaging technique (10) which can provide orthotropic images by measuring tissue backscattered light to obtain high-resolution crosssectional tomography images of the microstructure inside biological tissues. It is characterized by its biopsy ability, non-invasiveness, and real-time detection (11,12). The axial resolution of OCT can reach more than 10 times that of endoscopic ultrasound, reaching the micron level (13).…”
Section: Introductionmentioning
confidence: 99%